Some asymptotic formulae for the sums of multiplicative function and its applications - Fainleib, A. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. С. Файнлейб. Некоторые асимптотические формулы для сумм мультипликативных функций и их приложенияA. Fainleibas. Kai kurios asimptotinės formulės multiplikatyvinių funkcijų sumoms ir jų pritaikymai